English language communication training needs of front office assistants of hotels in Kuala Lumpur. - Chan, Mei-Yuit (Universiti Putra Malaysia Press, 2002)
In this study, English language communication training needs of Front Office Assistants were identified and described. Eight hotels of 4-star and 5-star rating in Kuala Lumpur participated in the survey, from which a total of 44 Front Office Assistants and 26 Managers responded. The main aim of the study was to determine which areas of job-based communicative activities deserve emphasis in a training programme for Front Office assistants. Also, the difference in perceptions between the Front Office Assistants and their managers regarding the training needs was explored. Data were collected via needs assessment questionnaire which requested a rating by the respondents of the proficiency level of Front Office Assistants on 35 communicative activities, and the relevance of these activities to the job of Front Office Assistant. The result was a description of the English language communication training needs of the subjects comprising the degree of training need for each communicative activity and the rank order of the activities according to training importance.